"Burnout" in children's home houseparents - Bath, Peter John (Rhodes University, Faculty of Humanities, Department of Psychology, 1983)
Aimed at replicating the results of an American study into "Burnout" in Group Home houseparents, this research had the following aims: 1) To ascertain the validity and reliability of the instrument used in the original study and presented as a "useful measure of burnout" . 2) To establish whether this line of research, within a highly problematic research field, can at present offer any guidelines in the resolution of the current staffing crisis faced by South African children's homes. 3} To describe more closely the burnout syndrome. 4) To study possible etiological factors within a local context. Sixty three houseparents completed questionaires and three independent measures of burnout were obtained. The results were regarded as having failed to replicate those of the original study. The reason for this was found to be the low validity of the original instrument. The main conclusion drawn was that the line of research adopted in the original study can offer only very tentative guidelines towards the resolution of the staffing crisis faced until such time as valid and reliable instruments to measure burnout have been developed. Many of the suggested relationships between situational variables and ones of personal characteristics were confirmed for the local population of houseparents.
Keywords: Burn out (Psychology); Children -- Institutional care; Houseparent; Foster parents; Child care workers -- Mental health